Emotional intelligence and self-monitoring behaviour: is there any link? - Mukherjee, Kumkum; Puri, Roma (2002)
Contrary to the traditional belief, managerial success is found to depend largely on Emotional Intelligence, rather than intelligence knowledge or skill. Technical skills or intelligence are not irrelevant, but mainly are `threshold capabilities' or entry level requirements while emotional intelligence (which is a subjective feeling state that can influence one's perception, thinking and behaviour) is important in achieving success over a longer period of time. Self-Monitoring behaviour refers to an individual's ability to adjust his/her behaviour to external situational factors and is also believed to be contributing significantly to managerial success. In the present study an attempt has been made to examine the possible relationship between different components of emotional Intelligence and Self-Monitoring Behaviour. The sample of the study comprises 57 MBA Final Year Students (both male and female) from Calcutta with an average age of 23 years. Emotional intelligence and Self-Monitoring Behaviour were measured with the help of Standardized questionnaires. The findings indicate the existence of a moderate but significant relationship between Emotional Expression and Self-Monitoring Behaviour while Emotional Self-Awareness is found to be negatively correlated with Self-Monitoring Behaviour. This is in accordance with what can be logically expected. - Reproduced. be logically expected. - Reproduced.
Keywords: Management